Differences of opinion make a horse race - Harris, M.; Raviv, A. (Review of Financial Studies, 1993)
A model of trading in speculative markets is developed based on differences of opinion among traders. Our purpose is to explain some of the empirical regularities that have been documented concerning the relationship between volume and price and the time-series properties of price and volume. We assume that traders share common prior beliefs and receive common information but differ in the way in which they interpret this information. Some results are that absolute price changes and volume are positively correlated, consecutive price changes exhibit negative serial correlation, and volume is positively autocorrelated.